Responses of soil biochemical properties and Cichorium intybus L. growth to polyethylene microplastic pollution - Song, Zixia; Wang, Mengyang; Li, Faguang; Long, Jianghu; Luo, Yang; Yang, Xiongyan; Tian, Xue (Frontiers in Plant Science, 2025)
Microplastics (MPs) have become a prominent topic of interest due to their effects on soil ecosystems and plant growth. In this study, using a pot experiment, we investigated the responses of the high-quality forage Cichorium intybus to different amounts (0.15%, 0.75%, 1.5%, 4.5%, 7.5%) of polyethylene microplastics (PE-MPs) in the soil, and sought to identify the underlying mechanisms. We found that PE-MPs did not significantly affect the growth of C. intybus at application rates of ≤1.5%. However, at the concentration of 4.5%, PE-MPs significantly reduced C. intybus height and root length. The fresh weight of the aboveground parts significantly decreased (by 25.06%) compared with the CK. At a PE-MP dosage of ≥1.5%, the chlorophyll a and total chlorophyll contents in the leaves of C. intybus declined significantly. Compared with the CK, PE-MP treatment increased the malondialdehyde content in the leaves of C. intybus by 60.04% to 306.47%, while superoxide dismutase activity also tended to increase. Meanwhile, the addition of PE-MPs significantly increased soil organic matter, decreased the pH and the alkali-hydrolysable nitrogen content, and reduced nitrogen concentrations in the aboveground parts of the plant. High-throughput sequencing analysis indicated that PE-MP treatment also reduced bacterial community diversity in the rhizosphere soil of C. intybus. At the phylum level, the abundance of Proteobacteria and Patescibacteria was significantly increased, whereas that of Gemmatimonadota and Chloroflexi showed the opposite trend. At the genus level, the relative abundance of the norank_WD2101_soil_group was increased, while that of RB41 and Gemmatimona was decreased, reflecting deteriorating soil quality. Our findings provide a theoretical basis for revealing the ecotoxicological effects of MPs on forage.